Effect of α-lactalbumin hydrolysate-calcium complexes on the fermentation process and storage properties of yogurt. (February 2018) - Zhao, L.L.; Wang, X.L.; Liu, Z.P.; Sun, W.H.; Dai, Z.Y.; Ren, F.Z.; Mao, X.Y.
Abstract: The effect of α-lactalbumin hydrolysate-calcium (α-LAH-Ca) complexes on the growth of lactic acid bacteria, fermentation kinetics, rheological and storage properties of yogurt was investigated. The α-LAH-Ca complexes exhibited growth-promoting activity on Streptococcus thermophilus ( S. thermophilus ), while a negative growth effect of Lactobacillus bulgaricus ( L. bulgaricus ) was observed. The complexes increased the maximum acidification rate (Vm), average acidification rate ( 0 T/h), and titration acidity (TA) significantly, but they shortened the fermentation period, time to pH 4.6 (TpH4.6 ), and time to Vm (Tvm ) ( P < 0.05 ). Compared with the control without complexes supplement, yogurt with an addition of 20 mg/100 mL complexes exhibited no significant difference in storage modulus (G′) and yield stress ( P > 0.05 ). In addition, the addition of complexes at 10 mg/100 mL and 20 mg/100 mL decreased whey separation ( P < 0.05 ) and obtained a similar viscosity to the control during the later period of storage. Reduction of post-acidification and L. bulgaricus viable counts in yogurt with added α-LAH-Ca complexes was also observed during the storage period ( P < 0.05 ). The addition of an appropriate amount of α-LAH-Ca complexes accelerated the fermentation process, attenuated post-acidification, and stabilized the storage properties of yogurt. Therefore, α-LAH-Ca complexes may possess good potential as a calcium-enriched vehicle in yogurt production. Highlights: α-lactalbumin hydrolysate-calcium (α-LAH-Ca) complexes promote S. thermophilus growth. Its addition produced similar rheological properties and viscosity, less whey separation compared to control. It accelerates fermentation, attenuates postacidification, and stabilizes storage properties of yogurt.